Indigenous Black Theology - Clark, J. author. aut Link
XVII, 186 p.
Keywords: This work is concerned with the way Black Christian formation, because of the acceptance of universal, absolute, and exclusive Christian doctrines, seems to justify and even encourage anti-African sentiment.